2021
DOI: 10.3390/jpm11080750
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Professional Boredom among Nursing Personnel in Greece

Abstract: Occupational (professional) boredom results in low performance at work. It has been positively associated with high levels of anxiety and depression as well as premature death. However, occupational boredom has not been extensively studied among working nurses. This study aimed to investigate the relationship between emotional intelligence and occupational boredom in nurses working in both public (52.9%) and private (47.1%) health units in Greece. A cross-sectional study was conducted among a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…Remache Agualongo et al (2023) explican que posibilita un trabajo en equipo con éxito a la vez que configura un cuidado oportuno de calidad y con calidez. Algunos estudios como los realizados por Soto-Rubio et al, (2020) y Papathanasiou et al,(2021) lo consideran como un factor protector fundamental frente a los riesgos psicosociales y lo han relacionado con una buena salud física y psicológica, la satisfacción laboral, el aumento del compromiso laboral y la reducción del burnout.…”
Section: Discussionunclassified
“…Remache Agualongo et al (2023) explican que posibilita un trabajo en equipo con éxito a la vez que configura un cuidado oportuno de calidad y con calidez. Algunos estudios como los realizados por Soto-Rubio et al, (2020) y Papathanasiou et al,(2021) lo consideran como un factor protector fundamental frente a los riesgos psicosociales y lo han relacionado con una buena salud física y psicológica, la satisfacción laboral, el aumento del compromiso laboral y la reducción del burnout.…”
Section: Discussionunclassified
“…Furthermore, a study on Chinese nurses demonstrated that those with high EI level were more able to communicate and had more empathy ability with their patients, and this led to more feeling of high personal achievement and more job satisfaction and wellbeing (Xie et al, 2021). Additionally, a study in no nursing personnel in Greece revealed that high EI can significantly decrease their professional boredom, and consequently improve their performance and personal achievement (Papathanasiou et al, 2021). Lastly, Khademi et al (2021) in a study of EI and nursing care in Iran demonstrated that EI had a positive impact on nurses' performance.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the individuals with the higher level of emotional intelligence could approach their works creatively in order to make the work more interesting while adopting positive perspectives and do not find the complex task as an overwhelming thing which otherwise it would discourage them. (Papathanasiou et al, 2021) The source of positive psychological capital was conceptually consisted of self-efficacy (individual ability), expectation, optimism, and resilience. According to Luthans, et al, the psychological capital has been built to create a profit competition for the organization or institution through development of expectation, optimism, endurance, and self.…”
Section: Internal Factormentioning
confidence: 99%